THE INFLUENCE OF SELF-EFFICACY ON STUDENTS' WORK READINESS - Annisa Nur Fitriyana; Kurjono Kurjono; Budi Santoso (LP2M IAI Al Khairat Pamekasan, 2021)
The purpose of this study was determine the effect of self efficacy on work readiness of vocational students. This research is quantitative research. The population in this study were all students of the 11th grade of the all department at SMK Al Ghazaly as many as 90 students. The population is limited less than 100, all subjects in this study were used as research samples This research use descriptive and verificative methods. The sample of the Analytical techniques used are simple linear regression. Normality test uses the Kolmogorov-smirnov test and simple linear regression. All data calculation using IBM SPSS v. 25 for Windows. The result showed that self efficacy effect toward work readiness The magnitude of the influence of self efficacy against the results of work readiness by 0,275 (27,5%) while the remaining 0,725 (72,5%) is affected by other factors.